Optimization of Arginine deiminase production from a local higher productive isolate Enterococcus faecium M1 - Mahdy, Nada Z. (Iraqi Journal of Cancer and Medical Genetics, 2014)
Arginine deiminase (ADI) is an important enzyme in many biological applications and a cancer treatment agent, recently increasing attention is focused to choose a higher productive strain from different bacterial sources. Eighty nine Enterococcus isolates were obtained from 215 samples (20 clinical UTI specimens, 52 human stool specimens, 6 soil and 11 from sewage water), fifty seven isolates were ADI producer. Twenty five isolates were more active in enzyme production, fourteen of them were identified as E. faecium and 11 isolates were E. faecalis. E. faecium isolate M1 obtained from UTI was the most efficient in ADI production, the specific activity of ADI produced from this isolate was 2.64U/mg protein. The effect of culture medium (Mineral salt broth) components on ADI production and other cultural conditions were determined to find the optimum conditions for enzyme production. The maximum ADI production was achieved when the medium was supplemented with 20mM arginine, 1% sucrose, 1% casein, pH 7.5 and incubated at 37ºC for 18 hours. Under these conditions, the specific activity of ADI was 5.1U/mg protein. By concluding, the present study was designed to select ADI higher productive isolate and optimum culture conditions for increasing the production of this enzyme in order to use it as a potent cancer treatment agent after purifying and characterizing it in the future.